2018
DOI: 10.1042/bcj20170935
|View full text |Cite
|
Sign up to set email alerts
|

The functional principle of eukaryotic molybdenum insertases

Abstract: The molybdenum cofactor (Moco) is a redox-active prosthetic group found in the active site of Moco-dependent enzymes, which are vitally important for life. Moco biosynthesis involves several enzymes that catalyze the subsequent conversion of GTP into cyclic pyranopterin monophosphate (cPMP), molybdopterin (MPT), adenylated MPT (MPT-AMP), and finally Moco. While the underlying principles of cPMP, MPT, and MPT-AMP formation are well understood, the molybdenum insertase (Mo-insertase)-catalyzed final Moco maturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 50 publications
1
59
0
Order By: Relevance
“…Within the Cnx1E active site, MPT-AMP adopts a conformation that is different from the one found in the Cnx1G MPT-AMP co-structure [11] and that properly orients the dithiolene motif toward enzyme bound molybdate [14,15]. Subsequently the MPT-AMP phosphoric anhydride bond is hydrolyzed, a reaction that is believed to be the prerequisite for enzyme catalyzed molybdate insertion into the MPT dithiolene motif [13][14][15]. Recent work suggested that the Cnx1E catalyzed molybdate insertion reaction involves the relocation of molybdate from the initial oxo-anion binding site to the insertion site [15].…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Within the Cnx1E active site, MPT-AMP adopts a conformation that is different from the one found in the Cnx1G MPT-AMP co-structure [11] and that properly orients the dithiolene motif toward enzyme bound molybdate [14,15]. Subsequently the MPT-AMP phosphoric anhydride bond is hydrolyzed, a reaction that is believed to be the prerequisite for enzyme catalyzed molybdate insertion into the MPT dithiolene motif [13][14][15]. Recent work suggested that the Cnx1E catalyzed molybdate insertion reaction involves the relocation of molybdate from the initial oxo-anion binding site to the insertion site [15].…”
Section: Introductionmentioning
confidence: 95%
“…In vivo interaction studies revealed the plant MPT synthase complex and the molybdenum insertase (Mo-insertase) to interact with each other, thus providing the framework necessary for efficient, protected and directed metabolite transfer [6]. The molybdate insertion reaction involves both functional domains of Mo-insertases, namely Eand G-domain [7] whose role for the Mo-insertion reaction has been studied in detail using the plant (Arabidopsis thaliana) Mo-insertase Cnx1 as model enzyme [8][9][10][11][12][13][14][15]. Notably, these domains are reactive as separately expressed domains (prokaryotes) or fused together (eukaryotes, except the lower alga Chlamydomonas reinhardtii [16]).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations